Association of Metabolic Dysfunction-Associated Fatty Liver Disease with Cognitive Impairment and All-Cause Dementia: A Comprehensive Review - Kaya, Eda; Yılmaz, Yusuf (Turkish Journal of Gastroenterology, 2024)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is a significant public health concern, affecting one-third of the global population and posing a risk for progressive liver disease. MAFLD is characterized by hepatic steatosis and impaired metabolic status, which not only impact the liver but also other systems of the human body, making it a multisystemic disorder. Emerging evidence suggests that MAFLD and its associated pathological pathways may contribute to cognitive impairment, potentially through neuroinflammation and neurodegeneration. Studies have detected cognitive impairment in patients with MAFLD using magnetic resonance imaging, which revealed decreased brain volume and cerebral perfusion, in addition to self-reported cognitive tests. While numerous studies have demonstrated an association between MAFLD and cognitive impairment, the relationship between MAFLD and all-cause dementia remains controversial. However, the shared pathological pathways between MAFLD and dementia, such as systemic inflammation, insulin resistance, gut dysbiosis, hyperammonemia, and vascular dysfunction, indicate the possibility of a common prevention strategy for both diseases. In this review, we provide a summary of the current evidence regarding the association between cognitive impairment, all-cause dementia, and MAFLD. Cite this article as: Kaya E, Yılmaz Y. Association of metabolic dysfunction-associated fatty liver disease with cognitive impairment and all-cause dementia: A comprehensive review. Turk J Gastroenterol. 2024;35(2):76-82.